1981
DOI: 10.1007/bf00313322
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the diagnostic value of drug-induced sleep EEGs and sleep EEGs following sleep deprivation in patients with complex partial seizures

Abstract: The purpose of the study was to investigate whether the sleep EEG after sleep deprivation has a stronger provocative effect than the drug-induced sleep EEG. For this purpose a sleep EEG, induced by 2 mg/kg body weight of promazine hydrochloride, was recorded. On the following day a sleep EEG of the same patient was recorded after sleep deprivation of 24--26 h. If only patients whose wake EEGs were free from epileptic activity are considered, the rate of provocation was 58%. As epileptic activity could be recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…Several studies have suggested that TSD can be useful in activating IEDs in wakefulness, especially in patients with IGE (Degen et al, 1980;Degen et al, 1981;Degen et al, 1983;Degen et al, 1987;El-Ad et al, 1994;Fountain et al, 1998;Geller et al, 1969;Klinger et al, 1991;Pratt et al, 1968;Ropakiotis et al, 2000;Roth et al, 1986;Scollo Lavizzari et al, 1977;Tartura et al, 1980;Veldhuizen et al, 1983). Fountain et al (1998) found that 7% of subjects had IEDs during wakefulness only after TSD.…”
Section: Effects Of Sleep Deprivation On Interictal Epileptiform Discmentioning
confidence: 96%
See 2 more Smart Citations
“…Several studies have suggested that TSD can be useful in activating IEDs in wakefulness, especially in patients with IGE (Degen et al, 1980;Degen et al, 1981;Degen et al, 1983;Degen et al, 1987;El-Ad et al, 1994;Fountain et al, 1998;Geller et al, 1969;Klinger et al, 1991;Pratt et al, 1968;Ropakiotis et al, 2000;Roth et al, 1986;Scollo Lavizzari et al, 1977;Tartura et al, 1980;Veldhuizen et al, 1983). Fountain et al (1998) found that 7% of subjects had IEDs during wakefulness only after TSD.…”
Section: Effects Of Sleep Deprivation On Interictal Epileptiform Discmentioning
confidence: 96%
“…In a series of studies in the 1980s, Degen and colleagues compared the effects of TSD on EEGs of subjects with different seizure types and epilepsy syndromes (Degen et al, 1981;Degen et al, 1983;Degen et al, 1987). For most seizure types, they found that spontaneous sleep and sleepdeprived recordings produced similar activation rates (awakening grand mal, 77% versus 71%; atypical absence, 78% versus 72%; absence epilepsy, 69% versus 71%; CPS, 49% versus 51%).…”
Section: Effects Of Sleep Deprivation On Interictal Epileptiform Discmentioning
confidence: 97%
See 1 more Smart Citation
“…33 4 Martin showed no change in V0 2 max after 30 hours of sleep deprivation.' 73 Symons et al found that sleep loss of up to 60 hours did not impair the capability for physical work. 8 3 Pickett and Morris 23 1 found that cardiovascular endurance was not affected by total sleep deprivation of 30 hours, but it was affected by food and water deprivation of the same duration.…”
Section: 66mentioning
confidence: 98%
“…If other authors such as Merlis et al [1951] and Gloor et al [1958] found lower activation rates of 10 or 7%, respectively, then this was due to a different patient population, a greater number of rou tine recordings and the use of pharyngeal electrodes in the case of complex partial sei zures. In previous studies, we recorded epi leptic activity during sleep in 45 and 78.1 %, respectively, in patients with complex partial seizures [Degen and Degen, 1981] and those with atypical absences [Degen and Dcgen, 1983a] whose routine EEGs showed no epi leptic discharges.…”
Section: Introductionmentioning
confidence: 99%